The International Court of Justice (Czech Journal of International Relations, 1999)
In July 1998, a diplomatic conference convened by the UN General Assembly adopted the Rome statutes of the International Court of Justice. It proceeded from a proposal submitted by the Commission on International Law. The outcome of laborious negotiations was an extensive treaty with 128 articles.Once the Statutes come into force, which requires the deposition of 60 ratification documents or documents on admission and access, an 18-member International Court of Justice with its seat in The Hague commences its activity.The Court is a permanent institution which is authorized to judge the most serious international crimes, affecting the international community as a whole. The Court adopts a complementary attitude to the national criminal jurisdiction of state parties.The Court is entitled to judge crimes of genocide, crimes against humanity, war crimes and crimes of aggression. The facts of a case in the first three categories are listed in detail in the Statutes. The crime of aggression is to be specified at an evaluation and revision conference due to meet seven years after the Statues come into force. The addition of further crimes (for example, crimes of international terrorism) is not ruled out in future.The Court deals with cases in an investigation, court and appeals senate. Apart from the Court, there is an independent separate prosecutor's office which is responsible for the prosecution and investigation of the culprits. The Secretariat of the Court deals with administrative services.The Court can pass verdicts of prison sentences of up to thirty years, and in exceptional cases even life imprisonment.